A revision of Beilschmiedia (Lauraceae) for Thailand and Indochina - de Kok, Rogier (Thai Forest Bulletin (Botany), 2021)
A revision of the genus Beilschmiedia (Lauraceae) from Thailand and Indochina is presented with a summary of its taxonomic history, plus keys, full descriptions of each species, distribution maps, conservation assessments, ecological information, ethno-botanical notes and a discussion of its morphology. In this treatment, 21 species are recognized; 14 names are lectotypified (B. argentata, B. balansae, B. balansae var. muticarpa, B. clarkei, B. elegantissima, B. ferruginea, B. globularia, B. glomerata var. tonkinensis, B. lucidula, B. obovalifoliosa, B. palembanica, B. poilanei, B. sphaerocarpa and B. wightii), five names are placed into synonymy for the first time, and B. laotica Kosterm. ex de Kok is validly published here for the first time. In addition, one new variety (B. percoriacea var. percoriacea de Kok) is proposed and one new combination (B. percoriacea var. glaucoides de Kok) is made. Nine species are considered to be Least Concern, one is Critically Endangered, five are Endangered, and five are listed as Vulnerable.